2017
DOI: 10.1103/physrevapplied.7.064022
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin Al2O3 Films for Tunnel Junctions

Abstract: Metal-Insulator-Metal tunnel junctions (MIMTJ) are common throughout the microelectronics industry. The industry standard AlO x tunnel barrier, formed through oxygen diffusion into an Al wetting layer, is plagued by internal defects and pinholes which prevent the realization of atomically-thin barriers demanded for enhanced quantum coherence. In this work, we employed in situ scanning tunneling spectroscopy along with molecular dynamics simulations to understand and control the growth of atomically thin Al 2 O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Surface-based, scanning techniques can be utilized to investigate barrier properties, both after formation as well as in-situ during growth. For example, scanning tunneling spectroscopy analysis of ALD Al2O3 and native aluminum oxide layers delineated differences between their potential barrier heights, where ALD films exhibited a value of approximately 1.42 eV in contrast to those found on thermally oxidized AlOx (0.67 eV) [272]. Used in combination with ballistic electron emission microscopy (BEEM), studies revealed inhomogeneous barrier properties that can vary from grain to grain in thin AlOx films [273].…”
Section: Characterizationmentioning
confidence: 99%
“…Surface-based, scanning techniques can be utilized to investigate barrier properties, both after formation as well as in-situ during growth. For example, scanning tunneling spectroscopy analysis of ALD Al2O3 and native aluminum oxide layers delineated differences between their potential barrier heights, where ALD films exhibited a value of approximately 1.42 eV in contrast to those found on thermally oxidized AlOx (0.67 eV) [272]. Used in combination with ballistic electron emission microscopy (BEEM), studies revealed inhomogeneous barrier properties that can vary from grain to grain in thin AlOx films [273].…”
Section: Characterizationmentioning
confidence: 99%
“…To address this issue, an in vacuo ALD process has recently been developed [32] that is capable of creating a negligibly defective IL at the electrode/M2 interface. This process leads to a high, thicknessindependent tunnel barrier height as the Al 2 O 3 thickness is varied from 0.1-1.0 nm in Josephson junctions [26,27]. An ultrathin pristine Al 2 O 3 film with negligible defects also exhibits high-quality dielectric properties with a high dielectric constant of ∼8.9, close to the bulk value of 9.2 observed in 3-4 nm thick Al 2 O 3 capacitors [33].…”
Section: Introductionmentioning
confidence: 77%
“…For many metals, native metal oxides will form on the electrode surface if it has been exposed to ambient conditions prior to the ALD deposition of the M1/M2 active layer. The native oxides are often defective, leading to incomplete ligand exchange and nonuniform deposition during the first few ALD cycles [26,27]. Typically, to combat the effects of undesirable defects, a thicker active layer measuring 4-12 nm or thicker is used [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum oxide is an important dielectric material which is widely used in the micro-and optoelectronics. [1,2] At present, α-Al 2 O 3 (corundum) is presumed to be a promising candidate for novel electronic devices due to its high electrical resistivity and dielectric constant, high strength and corrosion resistance, nontoxicity, and low cost. [3][4][5] In recent years, the electronic and optical properties of aluminum oxide doped with transition metals (TMs) have been intensively investigated.…”
Section: Introductionmentioning
confidence: 99%